Underutilized Leafy Vegetables in Western Ghats Region for Nutritional Security: A Recent Study - R. Balakumbahan; V. Sivakumar; C. Ravindran; J. Rajangam (Research Highlights in Agricultural Sciences Vol. 7, 2023)
Study has been undertaken to evaluate the nutritional value of some underutilized leafy vegetables available in Theni district of western Ghats region. Fifteen underutilized leafy vegetables used by the native people were collected and studied for their growth, yield and nutritional parameters. Among the evaluated underutilized leafy vegetables, the highest fresh foliage yield was registered in the Alternanthera bettzickiana. Ascorbic acid content was highest in Acalypha indica with lower fiber content. Carotenoid content and sodium content was recorded maximum in Hibiscus cannabinus. The highest total phenolic content was found in G13 Sauropus androgynus. Cardiospermum halicacabum has the highest potassium and copper content. The highest magnesium and manganese content was found in Talinum fruticosum. G15 Solanum trilobatum had the highest levels of zinc and calcium. The highest iron content was found in Alternanthera sessilis.